Performance of Phytogreen Zone for BOD5 and SS Removal for Refurbishment Conventional Oxidation Pond in an Integrated Phytogreen System - Abdul Syukor, Abd Razak; Zularisam, A. W.; Ideris, Zakaria; Mohd Ismid, M. S.; Nakmal, H. M.; Suryati, Sulaiman; Hasmanie, Abdul Halim; Siti Norsita, M. R.; Nasrullah, M. (World Academy of Science, Engineering and Technology, 2014)
In this study, the effectiveness of an integrated aquatic plants in phytogreen zone was studied and statistical analysis for the promotional integrated phytogreen system approached was discussed. It was found that's the effectiveness of using aquatic plant such as Typha angustifolia sp., Lepironia articulata sp., Limnocharis flava sp., Monochoria vaginalis sp., Pistia stratiotes sp., and Eichhornia crassipes sp., in the conventional oxidation pond process in order to comply the standard A according to Malaysia Environmental Quality Act 1974 (Act 127); Environmental Quality (Sewage) Regulation 2009 for effluent discharge into inland water near the residential area was successfully shown. It was concluded that the integrated phtogreen system developed in this study has great potential for refurbishment wastewater in conventional oxidation pond.